2000
DOI: 10.1038/35041572
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functions of the two isoforms of dopamine D2 receptors

Abstract: Signalling through dopamine D2 receptors governs physiological functions related to locomotion, hormone production and drug abuse. D2 receptors are also known targets of antipsychotic drugs that are used to treat neuropsychiatric disorders such as schizophrenia. By a mechanism of alternative splicing, the D2 receptor gene encodes two molecularly distinct isoforms, D2S and D2L, previously thought to have the same function. Here we show that these receptors have distinct functions in vivo; D2L acts mainly at pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
619
3
10

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 643 publications
(662 citation statements)
references
References 27 publications
30
619
3
10
Order By: Relevance
“…Maternal effect in Fragile X syndrome B Zupan and M Toth Starke et al, 1989;Usiello et al, 2000). These experiments indicated that the D2 receptor or its coupling/signaling may be the molecular target of the maternal effect.…”
Section: Introductionmentioning
confidence: 95%
“…Maternal effect in Fragile X syndrome B Zupan and M Toth Starke et al, 1989;Usiello et al, 2000). These experiments indicated that the D2 receptor or its coupling/signaling may be the molecular target of the maternal effect.…”
Section: Introductionmentioning
confidence: 95%
“…The D 2 gene itself can be alternatively spliced. Evidence indicates that the short form of D 2 (D 2 S) often serves as the presynaptic autoreceptor that inhibits DA release; whereas the long form (D 2 L) is more likely to be found postsynaptically (Khan et al, 1998;Usiello et al, 2000). Both D 1 -like and D 2 -like receptors are widely expressed in the brain with the relative abundance in the order of (Boyson et al, 1986;Richfield et al, 1989;Levey et al, 1993;Missale et al, 1998).…”
Section: Dopamine Receptors In the Striatummentioning
confidence: 99%
“…Whereas most antipsychotic compounds display equal affinity for both variants, clozapine and remoxipride, two compounds with a low propensity to cause EPS, bound with higher affinity to the D 2B than to the D 2A form of the receptor. Usiello et al (2000) found that the cataleptic effect of the typical antipsychotic haloperidol was absent in D 2A receptor deficient mice. These authors suggested that therapeutic activity could be related to blockade of presynaptic D 2B receptors, whereas extrapyramidal side effects could be avoided if the compound would fail to bind to D 2A receptors.…”
Section: Affinity For D 2a D 2b D 3 and D 4 Receptorsmentioning
confidence: 99%
“…Finally, differences in affinity for the two splice forms of the human D 2 receptor have also attracted attention (Malmberg et al 1993;Usiello et al 2000). Whereas most antipsychotic compounds display equal affinity for both variants, clozapine and remoxipride, two compounds with a low propensity to cause EPS, bound with higher affinity to the D 2B than to the D 2A form of the receptor.…”
Section: Affinity For 5-ht 2a Receptorsmentioning
confidence: 99%
See 1 more Smart Citation